Long‐term safety and sustained efficacy for up to 5 years of treatment with recombinant factor IX Fc fusion protein in subjects with haemophilia B: Results from the B‐YOND extension study - Pasi, K. John; Fischer, Kathelijn; Ragni, Margaret; Kulkarni, Roshni; Ozelo, Margareth C.; Mahlangu, Johnny; Shapiro, Amy; P’Ng, Stephanie; Chambost, Hervé; Nolan, Beatrice; Bennett, Carolyn; Matsushita, Tadashi; et al. (Haemophilia : the official journal of the World Federation of Hemophilia, 2020)
Introduction Recombinant factor IX Fc fusion protein (rFIXFc) has demonstrated efficacy for treatment of haemophilia B in the Phase 3 B‐LONG and Kids B‐LONG studies. However, long‐term rFIXFc safety and efficacy data have not yet been reported. Aim To report long‐term rFIXFc safety and efficacy in subjects with haemophilia B. Methods B‐YOND (NCT01425723) was an open‐label extension for eligibl previously treated subjects who completed B‐LONG or Kids B‐LONG. Subjects received ≥1 treatment regimen: weekly prophylaxis (WP), individualized interval prophylaxis (IP), modified prophylaxis or episodic treatment. Subjects could switch regimens at any time. The primary endpoint was inhibitor development. Results Ninety‐three subjects from B‐LONG and 27 from Kids B‐LONG (aged 3‐63 years) were enrolled. Most subjects received WP (B‐LONG: n = 51; Kids B‐LONG: n = 23). For subjects from B‐LONG, median (range) treatment duration was 4.0 (0.3‐5.4) years and median (range) number of exposure days (EDs) was 146 (8‐462) EDs. Corresponding values for paediatric subjects were 2.6 (0.2‐3.9) years and 132 (50‐256) EDs. No inhibitors were observed (0 per 1000 subject‐years; 95% confidence interval, 0‐8.9) and the overall rFIXFc safety profile was consistent with prior studies. Annualized bleed rates remained low and extended‐dosing intervals were maintained for most subjects. Median dosing interval for the IP group was approximately 14 days for adults and adolescents (n = 31) and 10 days for paediatric subjects (n = 5). Conclusions B‐YOND results confirm the long‐term (up to 5 years, with cumulative duration up to 6.5 years) well‐characterized safety and efficacy of rFIXFc treatment for haemophilia B.